Oxidative Coupling of Methane: Opportunities for Microkinetic Model-Assisted Process Implementations - Obradović, Ana; Thybaut, Joris W.; Marin, Guy B. (Chemical engineering & technology, 2016)
Oxidative coupling of methane is a low‐cost alternative for ethylene production. However, its high exothermicity, complex reaction network, and low selectivity to C2 products require more in‐depth analysis for economically viable process implementation. Microkinetic modeling enables assessment of operating conditions and catalyst properties on the overall performance via elementary gas‐phase and catalytic reactions. The know‐how to reproduce and interpret experimental kinetic data, especially the role of highly reactive intermediate species, is crucial for correct reaction network determination. Once the catalyst descriptors, physical catalyst properties, and operating conditions are determined and optimized, next catalyst generations can be developed tailored to the process implementation. Natural gas reserves are a rich source of methane that can be used as feedstock for the production of ethene via oxidative coupling. Finding a mathematical formula for a highly active and selective catalyst can save years of trial and error in catalyst research and reactor design. Microkinetic modeling is a powerful tool in the development of next catalyst generations.